(untitled) (Biological Sciences - PJSIR, 1999)
A hydrometallurgical method has been proposed for the 99% extraction a d recovery of copper from indige ous copper are using 5% solutions of trioctylaminc in benzene after. acid leac tng .of th.e ore with 7.5M H l: Various parameters, such as, the effect of temperature, acid concentration and digestion time have been optimiscd, The process developed has been made more cost effective by recycling used solvent.